Obstacles et facilitateurs perçus par les étudiants en situation de handicap à l’université et l’appréciation des services - Fournier, Anne-Louise; Hubert, Bruno; Careau, Louise (Canadian Journal of Education/Revue canadienne de l'éducation, 2020)
Recognizing the diversity of educational pathways for students with disabilities (SD), a large consultation was conducted with all students who consulted the office of support services of a Canadian university. Thus, 417 respondents completed an online survey. The findings highlight some barriers perceived by SD, such as financial barriers, inappropriate teaching methods and the fear of being discriminated against. However, a significant proportion of respondents report that they have experienced no barriers, and identify facilitators, such as support services, faculty openness and the use of accommodations. Keywords: student with disabilities, accommodation, postsecondary, inclusion